The coercive control of Daniel and Magdalena Lucek: A case of child abuse as tangential spouse abuse. (22nd September 2020) - Stark, Evan
Abstract: Drawing on a model developed by the author, coercive control was adapted in 2012 as the framework for a new "cross governmental" response in the health and social services to woman and child abuse in Great Britain, including changes in the criminal laws. I illustrate the forensic utility of the coercive control framework by applying it to explore the circumstances leading up to the murder of 4‐year old, Daniel Pelka (DP), in Coventry, England in 2009 and to critique the response by the various service providers to the family and the Crown's decision to try Daniel's mother, Magdalena Lucek, for the murder. Had the new approach been in place when the Lucek case came to public attention, the coercive control could have been recognized and effectively addressed.